2012
DOI: 10.1088/1468-6996/13/2/025005
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-loaded poly(lactide-co-glycolide)/poly(ethylene vinyl acetate) composite for stent coating by ultrasonic atomizing spray

Abstract: The mixture of poly(lactide-co-glycolide) (PLGA) and poly(ethylene vinyl acetate) (PEVA) forms a homogeneous liquid in an organic solvent such as tetrahydrofuran, and a phase-separated PLGA/PEVA composite can be prepared from it by evaporating the organic solvent. Exploiting this phenomenon, we designed a novel method of preparing a drug-loaded PLGA/PEVA composite and used it for coating drug-eluting stents (DESs). Paclitaxel (PTX), an anticancer drug, was chosen as a model drug. PLGA acts as a microdepot for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In order to evaluate the release profiles of paclitaxel-loaded PEVA compared to a blend of PEVA and PLGA (85:10), BMSs were spray coated and immersed in PBS (pH 7.4) with 0.05 wt.% Tween 80 at physiologic temperature and 120 rpm rotation [64]. The research showed that the PEVA control had 35% paclitaxel release in 5 days but only 40% total release by day 30.…”
Section: Stent Coating Techniquesmentioning
confidence: 99%
“…In order to evaluate the release profiles of paclitaxel-loaded PEVA compared to a blend of PEVA and PLGA (85:10), BMSs were spray coated and immersed in PBS (pH 7.4) with 0.05 wt.% Tween 80 at physiologic temperature and 120 rpm rotation [64]. The research showed that the PEVA control had 35% paclitaxel release in 5 days but only 40% total release by day 30.…”
Section: Stent Coating Techniquesmentioning
confidence: 99%
“…Several preclinical [33][34][35][36][37][38][39][40] and clinical studies [41][42][43] have used polyurethanes, silicones and PEVA as carriers for drug delivery in gastrointestinal malignancies. However, limited studies about localised drug delivery, particularly using these materials to oesophageal cancer have been conducted so far.…”
Section: Introductionmentioning
confidence: 99%
“…The implantation of a stent coated with antithrombogenic agents into the infected lesion has been explored to regulate platelet aggregation . However, stent implantation in the long run stimulates smooth muscle cell migration and the rupture of the atheroma thin layer, causing thrombosis and restenosis (i.e., renarrowing of blood vessels). , Even though numerous advanced strategies, such as antithrombogenic agents or immunosuppressive drugs including sirolimus onto the surface of the stent via the spray-drying method and electrophoretic deposition (EPD) techniques, have been attempted for drug-eluting stent (DES) and some of them are effective, there still remains an inherent need for advanced means against in-stent restenosis and thrombosis. …”
Section: Introductionmentioning
confidence: 99%